Pengaruh affective commitment dan organizational culture terhadap employee performance melalui work engagement pada karyawan - Laila Kurnia Sari; Budiono Budiono (Jurnal Ilmu Manajemen, 2025)
This study examines the influence of affective commitment and organizational culture on employee performance through employee work engagement (Study on one of the BUMN companies operating in the food sector). This study uses a quantitative causality design with a saturated sampling technique involving 75 permanent employees. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3 software. The results show that affective commitment has a positive and significant effect on employee work engagement and performance. Organizational culture also has a positive and significant effect on employee work engagement and performance. Furthermore, work engagement has a positive effect on employee performance. The analysis confirms that affective commitment and organizational culture indirectly improve employee performance through work engagement. These findings indicate that strengthening affective commitment and fostering an adaptive organizational culture can improve employee work engagement and performance.Keywords: Employee Performance, Work Engagement, Affective Commitment, Organizational Culture.